Determination of Azithromycin by Extractive Spectrophotometry - Uma Devi, P. (Asian Journal of Chemistry, 2010)
Two simple extractive spectrophotometric methods (M1 and M2) are developed for the determination of azithromycin (AZ) in bulk and dosage forms. They are based on the formation of coloured species with wool fast blue BL (WFBBL, M1) and tropileon 000 (TPOOO M2) reagents exhibiting maximum absorption at 580 and 480 nm, respectively. Methods M1 and M2 obeyed Beer's law limits 5-25 μg mL-1 and 10-40 μg mL-1, respectively. The proposed methods are simple, selective, sensitive and economical for the routine qualitative and quantitative determination of azithromycin in pharmaceutical formulations.